PENGARUH BUTIR SOAL DALAM FORMAT ANIMASI TERHADAP HASIL TES PEMAHAMAN KONSEP PEMBIASAN CAHAYA - Suhandi, Andi; Nur, Muhamad (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2010)
This study investigates the effect of computer animation on assessment of conceptual understanding in refraction phenomena. An instrument was developed by replacing static pictures and descriptions of ray motion on refraction phenomena with computer animations, a commonly used pencil and paper test. Both quantitative and qualitative data were collected. The animated and static versions of the test were given to students and the results were statistically analyzed. The questionnaire was also conducted to provide the student responses about using of animated version test on assessment of conceptual understanding in refraction phenomena. The results suggest that the use of the animation version of the test can be improving score of the conceptual understanding test in refraction phenomena. In general, students had a better understanding of the intent of the question when viewing an animation and gave an answer that was more indicative of their actual understanding, as reflected in the response of the questionnaire.Keywords: animation version test, conceptual understanding test, refraction phenomena